Performance of Simulated Bioremediation in Real Samples of Soils Contaminated with PAHs - de Souza Pohren, Roberta; de Oliveira Leite, Dilza Aparecida Nalin [UNESP]; de Franceschi de Angelis, Dejanira [UNESP]; Vargas, Vera Maria Ferrão (My University, 2016)
One of the possible ways of recovering the environmental quality of contaminated soils is the bioremediation process, in which soil pollutants are degraded using microorganisms. In this context, the evaluation of the bioremediation process efficiency was evaluated by preparing a consortium of autochthonous microorganisms of the soil from an area contaminated by wood preservatives. Subsequently, biodegradation experiments were performed on microcosm scale, applying bioaugmentation, enrichment and biostimulation techniques in two inoculums. The experiments were monitored by CO2production and the presence of total polycyclic aromatic hydrocarbons (PAHs). Organic extracts of this soil were prepared before and after being submitted to bioremediation, in which the 16 PAHs considered priority pollutants by USEPA were analyzed, and compared to the responses found for microbial respiration. The initial concentration of the PAHs was 34 mg/Kg. All the treatments achieved a removal rate above 60 %, and the mean degradation was 88 %. Statistical analyses of the results of CO2production showed a significant difference between all treatments for the control soil, except inoculum 1 (bioaugmented). However, inoculums 1 and 2 present a more efficient performance than the contaminated soil itself. When inoculums 1 and 2 (bioaugmented, biostimulated, and enriched) were compared, inoculum 2 presented a greater evolution of CO2and a better performance in PAHs degradation. Therefore, it was more efficient in the experiment. Hence, as the best results were obtained with the inoculum whose mixed culture had been enriched, this technique definitely has a greater potential for biodegradation in bioremediation processes with these contaminants.
Keywords: Autochthonous microorganisms; Biodegradation; Enrichment; Inoculum; Respirometry